Penggunaan Fuzzy Logic & Metode Mamdani untuk Menghitung Pembelian, Penjualan dan Persediaan - Maria Yus Trinity Irsan; Matius Irsan Kasau; Ika Pratiwi Simbolon (JAAF (Journal of Applied Accounting and Finance), 2019)
Fuzzy Logic is a development of Binary Logic that can be used to analyze data in research in both the exact and social fields. In this study, fuzzy logic is used to analyze data in a "Ayam Goreng Murah Rezeki" restaurant related to three linguistic attributes, each of which consists of two linguistic variables: Inventory (Little, Many), Sales (Down, Up), and Purchases (Reduced, Increased) using the Mamdani method. The purpose of the study is to provide an input value of Inventory and Sales to get a Purchase output value. The results of data analysis using a linear down graph and a linear upward graph on each linguistic variable with the Mamdani method yield results in the estimated area or range.